Anthracycline-induced cardiotoxicity - Hrdina, R; Gersl, V; Klimtová, I; Simůnek, T; Machácková, J; Adamcová, M (Acta medica (Hradec Kralove), 2000)
Anthracycline antibiotics are among the most effective and widely used antineoplastic drugs. Their usefulness is limited by a cumulative dose-related cardiotoxicity, whose precise mechanisms are not clear as yet. The principal role is possibly exerted by free oxygen radicals generated by "redox-cycling" of anthracycline molecule and/or by the formation of anthracycline-ferric ion complexes. The iron catalyzes the hydroxyl radical production via Haber-Weiss reaction. The selective toxicity of ANT against cardiomyocytes results from high accumulation of ANT in cardiac tissue, appreciable production of oxygen radicals by mitochondria and relatively poor antioxidant defense systems. Other additional mechanisms of the anthracycline cardiotoxicity have been proposed--calcium overload, histamine release and impairment in autonomic regulation of heart function. The currently used methods for an early identification of anthracycline cardiotoxicity comprise ECG measurement, biochemical markers, functional measurement and morphologic examination. Among a plenty of studied cardioprotective agents only dexrazoxane (ICRF-187) has been approved for clinical use. Its protective effect likely consists in intracellular chelating of iron. However, in high doses dexrazoxane itself may cause myelotoxicity. This fact encourages investigation of new cardioprotectants with lower toxicity. Orally active iron chelators and flavonoids attract more attention. Modification of dosage schedule and synthesis of new anthracycline analogues may represent alternative approaches to mitigate anthracycline cardiotoxicity while preserving antitumour activity.
Keywords: Antibiotics, Antineoplastic; monitorování léčiv; srdce; Animals; Drug Monitoring; lidé; Heart; Heart Diseases; Humans; zvířata; nemoci srdce; protinádorová antibiotika